Surgical treatment of elderly and senile patients with transtrochanteric fractures of the femur - Valovina, Yurii; Golynskyy, Andriy; Valovina, Nelia; Halii, Zorian; Smachylo, Stepan; Smahlii, Nazar (ScienceRise: Medical Science, 2023)
+ The aim of the work was to analyze the functional results of surgical treatment in elderly and senile patients with transcavitary fractures depending on the method of osteosynthesis. Materials and methods. 134 elderly and senile patients with transtrochanteric fractures of the femur type 31A1.1-A1.3 according to AO/ASIF were examined (average age - 72.4±9.3 years). The patient underwent osteosynthesis with a DHS fixator, a PFNA rod and a Gamma nail according to indications. The functional result of the treatment was determined by radiographic signs of fusion, the Harris scale, and complications detected during the period of 1, 3, 6, and 12 months of examination. Results and their discussion. The functional result according to the Harris scale dramatically prevailed in the first six months after surgical treatment with intramedullary osteosynthesis. For the DHS fixator, the indicator improved from 29.8 points in the first month to 57.7 at the sixth month, for the PFNA rod - from 50.7 points to 76.9, and for the Gamma nail from 50.1 to 76.7, respectively. Consolidation of a transtrochanteric fracture in treated elderly and senile patients was observed in 83.33 % of cases after extramedullary osteosynthesis, and in 90.22 % of cases after intramedullary osteosynthesis. Complications of extramedullary osteosynthesis included instability of the fixator with migration and fracture of the fixator, during intramedullary osteosynthesis – migration of the cervical blade "cut-out" and fracture of the rod. Conclusions. The functional result in elderly and senile patients with transtrochanteric fractures after intramedullary osteosynthesis has advantages over extramedullary osteosynthesis. The results of the calculation of the Harris scale indicators, among which the evaluation of the restoration of gait, movements and resistance of the injured limb were decisive, are significantly higher in osteosynthesis with a Gamma nail and a PFNA rod in comparison with a DHS fixator. Complications that occurred in the three groups of the study coincide with the average international indicators and are not significantly low with intramedullary osteosynthesis. Improvement of surgical treatment methods is urgent and requires the search for complex treatment approaches in elderly and senile patients with transtrochanteric fractures